The Influence Of Brand Positioning, Product Knowledge And Attitude On Green Product Purchase Intention Of Sensatia Botanicals - Nadia Ayu Wulandari; Dorothy Rouly H. Pandjaitan; Roslina (International Journal of Economics, Business and Innovation Research, 2025)
The escalating environmental crisis has driven a shift in consumer behavior towards eco-friendly products. Brands may perceive openings in the market, yet contradictions across prior scholarly outputs indicate unresolved ambiguity regarding what directs purchasing choices. This investigation intends to dissect how ecological brand positioning, comprehension of such brands, and disposition toward them interact to form the intention to acquire Sensatia Botanicals’ green-labeled commodities. Information was secured from 300 selected participants through purposive criteria and assessed via LISREL. The observed empirical outcomes demonstrate that positioning, knowledge, and attitudinal alignment with green brands all exert statistically significant positive impacts on the intention to procure environmentally branded goods. These results imply that companies should add strategies to communicate eco-friendly products effectively and efficiently by using social media influencers and digital media advertising. The communication strategy needs to highlight product quality and ethical production to justify premium pricing. Increased accessibility is key by expanding distribution through retail stores and e-commerce platforms. Additionally, companies must proactively build confidence in product performance with evidence-based marketing and authentic reviews.